Tephra without Borders: Far-Reaching Clues into Past Explosive Eruptions - Ponomareva, Vera; Portnyagin, Maxim; Davies, Siwan M. (Frontiers in Earth Science, 2015)
This review is intended to highlight recent exciting advances in the study of distal (>100 km from the source) tephra and cryptotephra deposits and their potential application for volcanology. Geochemical correlations of tephra between proximal and distal locations have extended the geographical distribution of tephra over tens of millions square kilometers. Such correlations embark on the potential to reappraise volume and magnitude estimates of known eruptions. Cryptotephra investigations in marine, lake and ice-core records also give rise to continuous chronicles of large explosive eruptions many of which were hitherto unknown. Tephra preservation within distal ice sheets and varved lake sediments permit precise dating of parent eruptions and provide new insight into the frequency of eruptions. Recent advances in analytical methods permit an examination of magmatic processes and the evolution of the whole volcanic belts at distances of hundreds and thousands of kilometers from source. Distal tephrochronology has much to offer volcanology and has the potential to significantly contribute to our understanding of sizes, recurrence intervals and geochemical make-up of the large explosive eruptions.